Cohesion and Coherence in the Writings of Iranain EFL Students - Arab Zouzani, Mohammad Ali (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study was conducted in to investigate the relationship of cohesive chains and chain interaction to the coherence of texts. To do this, the following procedure was followed. First, 95 EFL students were asked to write a composition on a particular topic. These texts were scored by three experienced raters based on their perceived degree of coherence. The texts were then ordered from high to low. Thirty high-rated texts were labeled as group A, and thirty low-rated texts were labeled as group B. These texts were analyzed for the presence and frequency of cohesive chain and chain interaction based on the model proposed by Hassan (1989). After collecting the data and statistically analyzing them, the results showed that the texts getting higher coherence scores had a higher proportion of relevant tokens to peripheral ones and a higher proportion of central tokens to non-central ones in comparison to the low-rated texts. Therefore, cohesive chain and chain interaction can be used as an indicator of coherence and has pedagogical and theoretical implications.